Clasificamos residuos sólidos para cuidar nuestro medio ambiente - Díaz Quispe, Leonira (2019)
The present work is basically focused on the design and elaboration of technological prototypes that contribute to give alternative solutions to the problems that afflict our society, one of these alternative solutions is the use of solid waste, solid waste is understood as any object, material, substance or element resulting from the consumption, or use of a good in domiciliary, industrial, commercial, institutional activities, of services that the generator abandons, rejects or delivers and that is susceptible of use or transformation into a new good. The learning session “We use solid waste to take care of our environment” is designed for students in the third grade of primary education. Its purpose is to develop the capacities of : Determine an alternative of technological solution, Design the alternative of technological solution and Implement and validates the alternative of technological solution, so that the student is sensitized and contributes to the care and conservation of their environment. To achieve this objective, relationship strategies with their peers were used based on previous knowledge and students' own experiences, using a list of checks as an evaluation tool.